Definition and diagnosis of sarcopenia: Asia-Pacific perspectives - Wei-Fu Huang; Ying-Chen Chen; Chin-Sung Chang; Chih-Hsing Wu (Osteoporosis and Sarcopenia, 2025)
Sarcopenia is a progressive, age-related condition characterized by the loss of skeletal muscle mass, strength, and function. As Asia faces rapid population aging, sarcopenia has become an urgent public health concern. Over time, definitions and diagnostic criteria have evolved to emphasize muscle strength and physical performance rather than muscle mass alone. This review summarizes key updates in global and regional frameworks, including guidelines from the European Working Group on Sarcopenia in Older People (EWGSOP2) and the Asian Working Group for Sarcopenia (AWGS 2019). However, these strategies might be updated along with the release of AWGS 2025.We also review current methods for evaluating muscle health. Although dual-energy X-ray absorptiometry (DXA) remains a standard, it has limitations in reflecting true muscle quality and predicting outcomes. Novel techniques like deuterium-labeled creatine dilution show promise for more accurate assessment. The review highlights emerging muscle-related biomarkers—myokines such as interleukin-6 (IL-6), insulin-like growth factor-1 (IGF-1), irisin, myostatin, and gelsolin—which may improve diagnostic precision and therapeutic strategies.The Global Leadership Initiative on Sarcopenia (GLIS) introduced the first globally endorsed definition, incorporating muscle mass, strength, muscle-specific strength, and physical performance as a key outcome in 2024. This unified approach supports standardized diagnosis across clinical and research settings. Addressing sarcopenia alongside other age-related conditions is essential to prevent frailty and disability. Finally, the targeted multidomain interventions—particularly physical activity and nutrition—are critical for preserving function and quality of life in older adults.